2017
DOI: 10.3390/rs9101081
|View full text |Cite
|
Sign up to set email alerts
|

Vis-NIR Spectroscopy and PLS Regression with Waveband Selection for Estimating the Total C and N of Paddy Soils in Madagascar

Abstract: Visible and near-infrared (Vis-NIR) diffuse reflectance spectroscopy with partial least squares (PLS) regression is a quick, cost-effective, and promising technology for predicting soil properties. The advantage of PLS regression is that all available wavebands can be incorporated in the model, while earlier studies indicate that PLS models include redundant wavelengths, and selecting specific wavebands can refine PLS analyses. This study evaluated the performance of PLS regression with waveband selection usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 53 publications
5
48
3
Order By: Relevance
“…These results also suggested that over 92% of the waveband information from the soil reflectance spectrum was redundant and did not contribute to or disturb the prediction. These findings support previous findings that the performance of PLS models can be improved through waveband selection, and the most useful information in the Vis-NIR region (400-2400 nm) predicted less than 20% of the forage [30,70], water [71] and soil parameters [18]. Moreover, the spectral data efficiency is also expected to improve by the optimization of the waveband subset using the GA-PLS model [30].…”
Section: Waveband Selection With Cross-validated Calibration Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…These results also suggested that over 92% of the waveband information from the soil reflectance spectrum was redundant and did not contribute to or disturb the prediction. These findings support previous findings that the performance of PLS models can be improved through waveband selection, and the most useful information in the Vis-NIR region (400-2400 nm) predicted less than 20% of the forage [30,70], water [71] and soil parameters [18]. Moreover, the spectral data efficiency is also expected to improve by the optimization of the waveband subset using the GA-PLS model [30].…”
Section: Waveband Selection With Cross-validated Calibration Resultssupporting
confidence: 88%
“…Although partial least squares (PLS) regression is the most commonly used approach for soil spectral analyses, waveband selection can refine the performance of a PLS analysis [16][17][18]. The PLS regression method combines the most useful information from hundreds of wavebands into the first several PLS factors (or latent variables), whereas the less important factors might include background effects [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPD is defined as the ratio of the standard deviation of the measured TPH concentration to the RMSE computed between the predicted and measured concentrations [27]. The interpretation of RPD values strongly depends on the context [27,64]. RPD values above 2 and 3 are often considered as good and excellent predictions of TPH, respectively, and values below 2 as poor ones.…”
Section: Variability Of Leaf Pigment Contents and Tph Estimationmentioning
confidence: 99%
“…In this paper, R 2 c and R 2 p represent the coefficient of determination of the calibration set and the prediction set, respectively, and RMSE c and RMSE p represent the root mean square error of the calibration set and prediction set, respectively. Besides this, the RPD has been suggested to be at least 3 for agriculture applications; where 2 < RPD < 3 indicates a model with a good prediction ability; 1.4 < RPD < 2 is an intermediate model needing some improvement; and RPD <1.4 indicates that the model has a poor prediction ability [36].…”
Section: Model Evaluation Indexmentioning
confidence: 99%